AN INSIGHT ON ALGAL CELL DISRUPTION FOR BIODIESEL PRODUCTION - A, Aarthy; Kumari, Smita; Turkar, Prachi; Subramanian, Sangeetha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This review article deals with the effect that various cell disruption techniques have on the efficiency of lipid extraction. We have reviewed existing algal cell disruption techniques that aid the biodiesel production process. Methods: Current rise in demand for energy has led the researcher to focus on the production of sustainable fuels, among which biodiesel has received greater attention. This is due to its larger lipid content, higher growth rate, larger biomass production, and lower land use. Extraction of lipid from algae (micro and macro) for the production of biodiesel involves numerous downstream processing steps, of which cell wall disruption is a crucial step. Bead milling, high-pressure homogenization, ultra-sonication, freeze-drying, acid treatment, and enzymatic lysis are some methods of cell disruption. The cell disruption technique needs to be optimized based on the structure and biochemical composition of algae. Result: The lipid extraction efficiency varies depending on the algal species and the cell disruption technique used. Conclusion: In-depth research and development of new techniques are required to further enhance the cell disruption of the algal cell wall for the enhanced recovery of lipids. In addition, the operating costs and energy consumption should also be optimized for the cost-effective recovery.